Implementación de una empresa productora y comercializadora de bebidas alcohólicas preparadas, típicas de la ciudad de Loja. - Agila Agila, Carmen Rosa (2012)
In the existing business and competitive companies in our country are facing a growing number of challenges, which require solvents and timely solutions. Enterprise administrators are responsible for obtaining favorable results, need to know that the society of our country has been facing critical issues in economic, political and social, which has led to enterprises in the market opportunity changes involved in the modernization, modernization, ie, new implementations performed in order to survive in the market, besides being the forger of the development of our society by creating jobs, but often this has not been possible competition between the companies that have increased in recent times, where its purpose is to increase profits and not lose heart in their struggle to keep their products on the market. In the city of Loja and in most provinces of our country, especially in the southern region, the economy is based on the business, since production and productivity of enterprises is one of the most important development and advancement of all peoples so that in every society entrepreneurship stems from man with an entrepreneurial spirit dedicated to the production of goods or services designed to meet the needs and demands of the environment. One of the most important problems in the urban area of the city of Loja is the nonexistence of producers and marketers of alcoholic beverages prepared typical of the locality, as there are currently only establishments that sell alcoholic beverages are not characteristic of the region, because they carry only sell imported products, which creates a lack of initiative to create production companies and marketing of traditional alcoholic beverages, taking advantage of existing material in the middle. For the development of the country is of vital importance to the generation of new businesses, which will allow national, regional and particularly the urban area of Loja City, therefore the project to be implemented help strengthen its economy and generate jobs both requires the population of this sector. After completing a study of the problems that exist in the business of the town, it was determined the need to implement a producer and marketer of alcoholic beverages typical to provide quality products meet the standards of hygiene and sanitation, same for compliance with consumer expectations. In order to make possible the development of this project, methods and techniques used to ensure that all activities are fully met, as recommended by the scientific and social research, so we could gather information about the tastes and preferences consumers, for the study was employed urban population of the city of Loja, 2010 which is 142,660 inhabitants, this market segment the total given to people aged 18 - 65 years of age represent 55% of the population (78 463 inhabitants), was applied in this way we received 383 surveys necessary information for our study. It also raised the following objectives: Prepare a Draft Feasibility Study for the Implementation of a producer and marketer of Alcohol prepared, typical of the city of Loja, in the city of Loja. Conduct a market study to determine the supply and demand in the market. Conduct a technical study to determine the size, location and project engineering. Determine the legal and administrative structures that the Company will have to ensure operation. An economic study - Finance to determine the size of the investment, financing and project budgets. Perform respective financial assessment to verify the feasibility of the project. These objectives are fully met and as a result have the following indicators: The installed capacity allows you to have an output of 5005 gallons of traditional alcoholic beverages per year. The company is located in the Parish of Canton Valley Loja, Bolivar street between Salinas and Juan Emiliano Ortega, place that has paths first order, basic services and is indispensable in the market to supply. To implement it requires an investment of $ $ 18,310.87, which will house financing by partners with a contribution of $ 13,312 dollars, and external financing will be through a loan granted by the National Development Bank of $ 5,000 dollars for a period of 5 years and a rate of 5% interest. The cost of production for the first year is $ 58,788.27 dollars and the sale price established is $ 12.92 U.S. dollars. To set the working capital projections take into account the 2010 inflation rate corresponding to 3.88%. The Net Present Value of the project is $ 74,491.27 dollars, the internal rate of return on investment is 41.65%, the benefit cost is $ 1.20, meaning that for every dollar you get 20 cents of profit, investment will recover in 2 years, 1 month and 13 days, the run will support a project cost increase of 7.99% and a decrease in revenues of 6.88%.